The haunted hotel - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 1999)
When the guests of the Shangri-La Hotel are scared away by a white-haired female ghost, Dink and his friends investigate the mystery.
"A Stepping Stone Book"
Keywords: Ghosts -- Fiction; Hotels, motels, etc. -- Fiction; Mystery and detective stories